What do women in rural Tamil Nadu think about postmenopausal bleeding? A mixed-method study - R Sindhuri; Amol R Dongre (Wolters Kluwer Medknow Publications, 2021)
Introduction: Perception of women about postmenopausal bleeding (PMB) may have a greater influence on their treatment-seeking behavior. Objectives: The objective was to explore the perceptions of causes and treatment of PMB among menopausal women and to quantify its perceived reasons. Materials and Methods: It was a sequential exploratory mixed-method study design, with two group interviews (qualitative phase), followed by a survey among 1530 postmenopausal women (quantitative phase). The qualitative data were analyzed by thematic analysis and quantitative data using descriptive statistics. Results: Lack of seriousness about PMB and stigma were stated as barriers for the treatment of PMB. Among 1530 women, 40.8% of them did not know the cause for PMB. The problem in the uterus, cancer, and improved nutrition were stated as reasons by 17.6%, 16.8%, and 15.8% of women, respectively. Conclusion: Most of the women did not know the reason for PMB and its awareness is crucial for better uptake of screening and detection of pathology at an early stage.